Recursive Justification and Kant’s Civil Condition: Some Comments on Flikschuh’s Account of Nomadic Rights - Scott Johnston, James (Con-Textos Kantianos. International Journal of Philosophy, 2017)
Katrin Flikschuh presses Karl Amerik’s notion of recursive justification into service with respect to the question whether nomads have an obligation to enter statehood. Flikschuh answers in the negative, and claims that nomads, who have not entered into the civil condition, cannot be expected to conform to the obligations of statehood. I agree with Flikschuh’s claim, and provide further support through Kant’s arguments in the Lectures on Logic that such obligations as statehood are objective criteria of judging, and require the raising of subjective claims to practical reality—a condition that cannot be meet on the part of settlers alone.
Keywords: Kant; Katrin Flikschuh; Statehood; Civil Condition; Nomads; Recursive Justification; Lectures on Logic